Effect of ambient temperature variance on power output of wind turbine and mitigation strategy - Nyam Jargalsaikhan; Sergelen Byambaa; Baigali Erdenebat; Nomuulin Batjargal; Munkhjargal Sukhbaatar (Journal of Emerging Science and Engineering, 2025)
Many challenges have been found in the operation of wind turbine under varying weather conditions, which demands novel strategies to address these issues. As far as we know, the variation of weather parameters is crucial for wind turbine operators to monitor the operation of wind turbines and adjust parameters of generator to ensure safe and efficient operation. This study aims to explore the effect of ambient temperature variation on wind turbine parameters including rotational speed, output power and pitch angle, using 10-minute measurement data for temperature ranges from -5oC to +20oC. By understanding such effects, researches can develop a control strategy to minimize their effect and improve the performance of wind turbines by increasing power production and reducing unnecessary loads and control actions. In this research, the mitigation method was developed within the control system to correct the parameters of wind turbine according to ambient temperature variation, offering a more practical strategy for wind turbines that currently in use. The simulation studies were carried out using Matlab/Simulink® software, and the results revealed that the output power of the wind turbine rose by 5.71% compared to standard strategy after mitigation method was implemented.